Numerical Study on the Effect of Current Profiles on Vortex-Induced Vibrations in a Top-Tension Riser - Fu, Bowen; Zou, Lu; Wan, Decheng (Journal of marine science and application, 2017)
In this paper, numerical simulations of vortex-induced vibrations in a vertical top-tension riser with a length-to-diameter ratio of 500 using our in-house code viv-FOAM-SJTU are presented. The time-dependent hydrodynamic forces on two-dimensional strips are obtained by solving the Navier-Stokes equations, which are, in turn, integrated into a finite-element structural model to obtain the riser deflections. The riser is discretized into 80 elements with its two ends set as pinned and 20 strips are located equidistant along the risers. Flow and structure are coupled by hydrodynamic forces and structural displacements.In order to study the effects of the shear rate, of the current profiles on the vortex-induced vibrations in the riser, vibrations, with varying shear rates, in both the in-line and cross-flow directions,are simulated. In addition to the time domain analysis, spectral analysis was conducted in both the temporal and spatial domains.Multi-mode vibration characteristics were observed in the riser. The relationship between dominant vibration mode number and the shear rate of current profiles is discussed. In general, the overall vibrations in the riser pipe include contributions from several modes and each mode persists over a range of shear rates.Moreover, the results suggest that with a larger shear rate the position of the maximum in-line time-averaged displacement will move closer to the end where the largest velocity is located.